Sponges as bioindicators for microparticulate pollutants?. (1st January 2021) - Girard, Elsa B.; Fuchs, Adrian; Kaliwoda, Melanie; Lasut, Markus; Ploetz, Evelyn; Schmahl, Wolfgang W.; Wörheide, Gert
Abstract: Amongst other threats, the world's oceans are faced with man-made pollution, including an increasing number of microparticulate pollutants. Sponges, aquatic filter-feeding animals, are able to incorporate fine foreign particles, and thus may be a potential bioindicator for microparticulate pollutants. To address this question, 15 coral reef demosponges sampled around Bangka Island (North Sulawesi, Indonesia) were analyzed for the nature of their foreign particle content using traditional histological methods, advanced light microscopy, and Raman spectroscopy. Sampled sponges accumulated and embedded the very fine sediment fraction (<200 μm), absent in the surrounding sand, in the ectosome (outer epithelia) and spongin fibers (skeletal elements), which was confirmed by two-photon microscopy. A total of 34 different particle types were identified, of which degraded man-made products, i.e., polystyrene, particulate cotton, titanium dioxide and blue-pigmented particles, were incorporated by eight specimens at concentrations between 91 and 612 particle/g dry sponge tissue. As sponges can weigh several hundreds of grams, we conservatively extrapolate that sponges can incorporate on average 10, 000 microparticulate pollutants in their tissue. The uptake of particles, however, appears independent of the material, which suggests that the fluctuation in material ratios is due to the spatial variation of surrounding microparticles. Therefore, particle-bearing sponges have a strong potential to biomonitor microparticulate pollutants, such as microplastics and other degraded industrial products. Graphical abstract: Image 1 Highlights: Sponges accumulate non-negligible quantities of particulate micropollutants. Particles of anthropogenic origin, e.g., polystyrene and cotton, were identified. The incorporation of particles by sponges is independent of the material type. Sponges are strong bioindicators to monitor man-made pollution in marine realms.